Transvaginal radiofrequency ablation: a therapeutic option for managing symptomatic uterine fibroids in women with reproductive desires - Ma Eugenia Marín Martínez, M.D; Sara Cruz-Melguizo, M.D., Ph.D; Gema Vaquero Argüello, M.D; Virginia Engels Calvo, M.D., Ph.D; Ma Luisa De la Cruz Conty, Ph.D; Tirso Pérez Medina, M.D., Ph.D (Elsevier, 2024)
Objective: To evaluate whether transvaginal radiofrequency (RF) ablation of fibroids is a technique that can be offered to women with reproductive desires. Design: Unicentric, prospective, observational study. Setting: University Hospital. Patient(s): Twenty-seven individuals who desired to become mothers after undergoing RF ablation for symptomatic fibroids. Intervention(s): Transvaginal RF ablation for symptomatic fibroids with a maximum total volume of 145 cm3. Main Outcome Measure(s): The reduction in the size of the fibroids, improvement of symptoms, and reproductive outcomes during the 24 months after the ablation. For patients who achieved pregnancy, we assessed the type of conception, course of gestation, type of delivery, neonatal outcomes, and occurrence of both maternal and fetal complications. Result(s): A statistically significant reduction in symptoms related to the fibroids 6 months after the ablation was demonstrated through the implementation of the Symptom Severity Scale. No patient required hospitalization after the procedure, and on average from the third day after intervention, they resumed their work activities without the need for analgesics. Among those patients who attempted pregnancy during the 24-month follow-up period, 73.68 % (14/19) achieved motherhood. There were no cases of uterine rupture, premature birth, or intrauterine fetal death. Conclusion(s): Radiofrequency ablation for fibroids seems to be a promising, safe, and low-complexity alternative that does not appear to interfere with the development of a normal term gestation.